Fahr's Syndrome and Secondary Hypoparathyroidism - Santos Vitorino Modesto dos; Da Mata Ana Medeiros De Farias; Ribeiro Kelle Regina Alves; Calvo Isadora Cartaxo De Sousa (Sciendo, 2016)
A typical case of Fahr's syndrome is described in a 76-year-old Brazilian female who underwent a total thyroidectomy three decades ago. Six years before the current admission, she started with generalized tonic-clonic seizures. Associated disorders involved extra-pyramidal, cognitive, nocturnal terror and mood changes. With suspicion of hypocalcemia due to secondary hypoparathyroidism, laboratory determinations confirmed the diagnoses. Furthermore, imaging studies of the central nervous system detected multiple calcifications, with characteristic distribution of Fahr's syndrome. Clinical management was successful.